2019
DOI: 10.1111/micc.12587
|View full text |Cite
|
Sign up to set email alerts
|

Surface markers: An identity card of endothelial cells

Abstract: All endothelial cells have the common characteristic that they line the vessels of the blood circulatory system. However, endothelial cells display a large degree of heterogeneity in the function of their location in the vascular tree. In this article, we have summarized the expression patterns of a number of well‐accepted endothelial surface markers present in normal microvascular endothelial cells, arterial and venous endothelial cells, lymphatic endothelial cells, tumor endothelial cells, and endothelial pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 93 publications
1
20
0
Order By: Relevance
“…Previously, lipofibroblasts have been reported to be involved in alveolar development, regeneration, surfactant synthesis and vitamin A (retinoic acid) storage [33], and contribute to the alveolar epithelial cell II (AECII) stem cell niche in the adult mouse lung [34]. The enrichment result in endothelial cells was mainly related to vasculature development ( Figure 5E), which is consistent with the knowledge of endothelial cells as vasculature forming cells [35]. Several varied terms were identified among the enriched biological processes of Pdgfrb high (Pdgfrb hi) cells, suggesting that this cell type is a transitional cell type.…”
Section: Go Enrichment Analysis Identifies Different Roles Of the Eigsupporting
confidence: 89%
“…Previously, lipofibroblasts have been reported to be involved in alveolar development, regeneration, surfactant synthesis and vitamin A (retinoic acid) storage [33], and contribute to the alveolar epithelial cell II (AECII) stem cell niche in the adult mouse lung [34]. The enrichment result in endothelial cells was mainly related to vasculature development ( Figure 5E), which is consistent with the knowledge of endothelial cells as vasculature forming cells [35]. Several varied terms were identified among the enriched biological processes of Pdgfrb high (Pdgfrb hi) cells, suggesting that this cell type is a transitional cell type.…”
Section: Go Enrichment Analysis Identifies Different Roles Of the Eigsupporting
confidence: 89%
“…The gradual decline in expression of genes along with the projection proved that ECs are exhibiting a continuous phenotype, coined zonation (Vanlandewijck et al, 2018), rather than showing discreet phenotypes. Other patterns of markedly expressed genes that can be found in arteries are Ephrin B2, Alk1, Dll4, NRP1, Depp, Hey1 and Hey2, EPAS1 while veins express a pattern of Ephrin B2, Eph B4, NRP2, and COUP−TFII (Cheng et al, 2002;Aird, 2007;Ribatti et al, 2020).…”
Section: Intra-tissue Heterogeneity/heterogeneity Within the Vascularmentioning
confidence: 99%
“…In an effort to study heterogeneity within PCs, Vanlandewijck et al (2018) identified PCs among other cell types within murine brain samples by applying known PC gene patterns to their data set. Sorting for the presence of canonical PC markers such as Pdgfrb, Cspg4, and Des and excluding cells expressing smooth muscle cell (SMC) markers like Acta2 and TagIn, as well as fibroblast markers Cheng et al, 2002;Aird, 2007;Ribatti et al, 2020 Arteries Alk1 Cell-surface receptor Mouse Cheng et al, 2002;Aird, 2007;Ribatti et al, 2020 Arteries Dll4 Notch ligand Mouse Cheng et al, 2002;Aird, 2007;Ribatti et al, 2020 Arteries Nrp1 Neuropilin 1 Mouse Cheng et al, 2002;Aird, 2007;Ribatti et al, 2020 Arteries Depp Decidual protein induced by progesterone Mouse Cheng et al, 2002;Aird, 2007;Ribatti et al, 2020 Arteries Hey1 Transcription factor Mouse Cheng et al, 2002;Aird, 2007;Ribatti et al, 2020 Arteries Hey2 Transcription factor Mouse Cheng et al, 2002;Aird, 2007;Ribatti et al, 2020 Arteries…”
Section: Heterogeneity In Pericytesmentioning
confidence: 99%
See 2 more Smart Citations